Optimalisasi Pendekatan Scientific dalam Pembelajaran Pendidikan Agama Islam - Sarini Musyafi'ah Ali; Kartini Ponengoh (Tafhim Al-'Ilmi, 2020)
This study serves to determine the extent of the use of scientific approaches inlearning Islamic religious education. The method used in this research is to uselibrary research or library research. Where research uses reference books, articles,and journals related to the research title. The 2013 curriculum is a development ofthe Competency Based Curriculum which was first released in 2004 whichincludes competency attitudes, knowledge, and skills by using a scientificapproach in learning. Learning by using a scientific approach is a learning processthat is designed so that students are actively involved in contradicting principles,concepts, or laws by going through several stages of learning activities. The workprocess of this approach is to prioritize the logic of inductive thinking rather thandeductive. Learning with a scientific approach is a learning process that isdesigned so that students are actively involved in understanding the materialwithout relying on information conveyed by the teacher. The learning step with ascientific approach includes observing, asking, trying, reasoning (associating),concluding, and communicating (forming networks). The use of the scientificapproach is intended so that the material delivered by the teacher or educator canbe understood by students. Before carrying out learning activities using ascientific approach, the teacher must make some preparations by preparinglearning instruments such as lesson plans. Basically, all learning activities are leftto each teacher to be able to develop innovation and creativity. although thepreparation is not the same as the example, but it can provide a reference for theuse of a scientific approach